1992
DOI: 10.1111/j.1600-051x.1992.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

The immediate‐ and medium‐term effects of Meswak on the composition of mixed saliva

Abstract: Chewing sticks or Meswaks are used for teeth cleaning in many parts of the world. They contain substances that may reduce caries and periodontal disease. The present study consisted of 2 parts. In a short-term experiment, volunteers chewed on an inert eliciting agent (pyrogen-free rubber) and then a piece of Meswak, each for 5 min. For the medium-term experiment, volunteers brushed with either Meswak or a conventional toothbrush 5 x a day for 2 weeks. Saliva produced immediately after chewing Meswak showed sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
2
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 15 publications
1
37
2
3
Order By: Relevance
“…[22] Certain plant fibres such as miswak contain sodium bicarbonate which has mild abrasive properties as well as germicidal effect. [23] In the present study the mean plaque score difference between the subjects using only miswak and toothbrush with tooth paste groups was not statistically significant, but it was significantly different when both these groups were compared to group III. i.e.…”
Section: Discussioncontrasting
confidence: 62%
“…[22] Certain plant fibres such as miswak contain sodium bicarbonate which has mild abrasive properties as well as germicidal effect. [23] In the present study the mean plaque score difference between the subjects using only miswak and toothbrush with tooth paste groups was not statistically significant, but it was significantly different when both these groups were compared to group III. i.e.…”
Section: Discussioncontrasting
confidence: 62%
“…Al-Otaibi et al (2003) reported that miswak had a significant reduction of plaque (p < 0.001) and gingival (p < 0.01) indices compared to the toothbrush. Clinical studies on saliva showed that using miswak sticks or rinsing with aqueous miswak extract has an immediate inhibitory effect on salivary bacteria (Gazi et al, 1992;Darout et al, 2002;Almas and Al-Zeid, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Tannins were found to reduce gingivitis [25,26], vitamin C help in tissue healing [23], and silica and chloride removing stains and helpful in tooth whitening [6,27]. The essential oils in S. persica Miswak that has bitter taste stimulate the flow of saliva, which promote enamel remineralization [26,28].…”
Section: Discussionmentioning
confidence: 99%